BEETROOT (Beta vulgaris L.) AND ITS POTENTIAL AS AN ANEMIA TREATMENT IN PREGNANCY - Fadlilah, Synta Haqqul; Suhartomo, Dalri Muhammad; Yusan, Rizak Tiara; Yudhawan, Indra (Fakultas Kedokteran Universitas Jenderal Soedirman, 2023)
Anemia is one of the most common nutritional problems in pregnant women. It is defined as a condition in which the hemoglobin (Hb) level is lower than normal. The main cause of anemia in obstetrics is iron deficiency. To prevent this condition, the Government of Indonesia through the Ministry of Health made a rule by giving iron tablets to pregnant women at least 90 tablets during pregnancy (Kemenkes RI, 2022). However, some people are often bored with this pharmacological therapy due to the nausea and vomiting effect of the iron smell. Therefore, the development of alternative anemia therapy has been done to minimize those problems. One of the herbal ingredients that are being studied for its potential as anti-anemia in pregnancy is beetroot (Beta vulgaris L.). This research is included in the type of literature review. The selected literature is research articles published in the last 10 years (2013 to 2023). There are 10 articles that match the topic of study. A total of 7 publications demonstrated the effect of beetroot on anemia in pregnant women during the pregnancy period, and 2 articles in the post-partum period. A study performed in vivo experiments on pregnant female rats. Almost all of the studies did intervention by giving subjects beetroot juice. Only one study used beets as an intervention as ice cream. The results show that beetroot has the potential to prevent and treat anemia in pregnancy by increasing hemoglobin levels and the amounts of hematocrit. It contains a high level of folic acid which is important for normal cell and tissue growth. The iron content of beetroot also plays an essential role in the human body transporting oxygen to red blood cells, so it helps to cure anemia.